المنطق في الفكر العربي الإسلامي بين التقليد وإعادة التأسيس - الضاهر, سليمان; حريبا, لؤي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
بالرغم من الاهتمام الكبير الذي حظي به المنطق الأرسطي عبر مسيرة الفكر العربي الإسلامي؛ من قبل كل الاتجاهات الفكرية – مشائية, كلام, تصوف- إلا أننا نلاحظ بعض الأصوات التي دعت علانية إلى نبذ المنطق الأرسطي وتحريم العمل به. حيث قامت لدى كل الاتجاهات محاولات إما لاستيعاب المنطق ضمن النسق الفكري لكل الاتجاه؛ وذلك بالتركيز على أحد جانبيه وإهمال الجانب الآخر؛ وإما لاستبداله بمنطق بديل. وبين أصوات المعارضين والموالين للمنطق الأرسطي قامت عملية تكييف واسعة لجعل المنطق مقبولاً في حياتنا الفكرية, وليس أدل على ذلك من استمرار الاهتمام به وتدريسه حتى في فترات الانغلاق الفكري التي عرفها الفكر العربي في عصر الجمود. والتساؤل الذي نطرحه هنا هو حول عملية التكييف التي قامت, هل مسّت جوهر المنطق الأرسطي وأبعدته عن أسسه التي وضعها له أرسطو, بما يتيح لنا الحديث عن منطق إسلامي جديد مستقل ومختلف عن المنطق الأرسطي؟ أم أن عملية التكييف لم تتعدَ إعادة ترتيب الأجزاء وحذف بعض الأبحاث وتقريب المصطلحات, دون أن تتعدى ذلك إلى الإخلال بأسس المنطق كما وضعها المعلم الأول؟ Despite the attention given to logic across the Arab Muslim march of thought from all thought directions: peripatetic, speech, mysticism, we notice sounds, which are not few, call for rejecting Aristotelian logic and prohibiting working in it. Where there were attempts in all directions either for accepting the logic in the thought layout in each direction such as concentrating on one side and neglecting the other or replacing it with other logic. A wide adjustment process has done between the opponent sounds and the loyalists to it to make logic acceptable and there is no evidence more than the continued interest in it and teaching it even in the intellectual isolation periods defined by the Arab thought in the era of stagnation. The question here is about the adjustment process, did it touch the essence of Aristotelian logic and kept it away from the foundations established by Aristotle, allowing us to talk about a new separated Islamic logic different from Aristotelian logic? Or did the adjustment process not exceed reordering parts and deleting some researches and closing terms without exceeding to prejudice the foundations of logic as was placed by the first teacher?